BIOBRAS-16 IMPROVES THE ACCLIMATIZATION OF SPANISH CARNATION (DIANTHUS CARYOPHYLLUS L.) PLANTS OBTAINED IN VITRO - Valdés, Yanelis Castilla; González Vega, María Esther (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
The Spanish carnation (Dianthus caryophyllus L.) is one of the most commercialized flowers worldwide. Its accelerated propagation is possible due to the utilization of micropropagation methods, especially if combined with the employment of different bioproducts, between them the brassinosteroid analogous, known as Biobras-16. However, up to the moment, there is a lack of references about the acclimatization of Spanish carnation plants, micropropagated with this brassinosteroid analogue. For this reason, in the present work we proposed the aim of determine the survival of plants of Spanish carnation acclimatized with the employment of Biobras-16. The plants were obtained from meristems, cultured in medium with different concentrations of Biobras-16 (10-1; 10-2 and 10-3 mg·L-1), and from them, two propagations were made by cuttings, without the addition of Biobras-16 but respecting the treatments of origin of the plants. The plants obtained from the second propagation, were acclimatized under semi controlled conditions, using two assays: the first one, without treatment with Biobras-16, and the second one, with the application to the leaves of a solution with the same concentrations of Biobras-16 used in each treatment of the meristems culture. In general, in the control treatments was obtained an intermediate survival of the plants of Spanish carnation, confirming it is a bounding and transcendental stage for the successful culmination of the micropropagation process. In the first assay, the plants survival overcame significantly to the control in the treatmentwhich employed 10-3 mg·L-1 of Biobras-16 during the micropropagation. In the second assay, in the treatments where the plants were sprayed with 10-1 and 10-3 mg·L-1of brassinosteroid analogue, were obtained higher survival percentages than the obtained in the first assay. It was appreciated the feasibility of the use of the Biobras-16, because its use in the in vitro culture and its spraying during the acclimatization phase of the Spanish carnation vitroplants, it is capable to produce increases in the survival percentage between 12,5% and 17%, which increment the efficiency of the micropropagation process.